Ergonomic Assessment of Non Folding Electric Wheelchair Performance: Penilaian Ergonomis terhadap Kinerja Kursi Roda Listrik Non-Lipat - Anggit Prastio; A’rasy Fahruddin (Indonesian Journal of Innovation Studies, 2025)
General Background: Electric wheelchairs are widely used to support mobility and daily activities for individuals with physical disabilities. Specific Background: User comfort and operational capability of electric wheelchairs are strongly associated with ergonomic suitability, anthropometric compatibility, and technical performance under different operating conditions. Knowledge Gap: Previous studies have not sufficiently evaluated the relationship between user anthropometry, upper limb posture, and the mechanical performance of non folding electric wheelchairs for users with specific physical limitations. Aims: This study aimed to evaluate the ergonomic suitability and performance characteristics of a non folding electric wheelchair using anthropometric analysis, Rapid Upper Limb Assessment (RULA), and propulsion and steering performance testing. Results: The findings showed several mismatches between user body dimensions and wheelchair dimensions, particularly in footrest height, footrest length, and armrest height. RULA analysis produced a score of 4, indicating that posture modifications are required. Performance testing demonstrated that the wheelchair could carry loads up to 120 kg and travel approximately 15.36 km on a full battery charge, but limitations were identified in climbing ability, maximum speed, steering control, and obstacle clearance. Novelty: This study integrates ergonomic evaluation and technical performance testing on a non folding electric wheelchair designed for users with asymmetric physical conditions. Implications: The results provide practical recommendations for improving wheelchair ergonomics, steering stability, energy efficiency, and mechanical configuration to support safer and more comfortable mobility for users with disabilities.Highlights: Anthropometric comparison identified dimensional mismatches in armrest and footrest configuration. Postural evaluation indicated corrective adjustment requirements for upper body positioning. Mechanical testing revealed limitations in slope navigation, steering response, and maximum travel speed. Keywords: Electric Wheelchair; Ergonomic Assessment; Anthropometry; RULA; Wheelchair Performance